The development of PACCE learning model based on the Bugis local wisdom to promote student social awareness - Arman Abu Bakar; Susriyati Mahanal; Abdul Gofur; I. Ibrohim (Research and Development in Education (RaDEn), 2024)
The Makassar Bugis local wisdom, Pacce, contains values that are useful to instil self-confidence, a strong work ethic, and social awareness in individuals. The integration of these values into the learning process may assist in shaping student character. Unfortunately, research into learning models based on the Makassar Bugis local wisdom remains limited. Thus, the aim of this study was to generate a learning model based on the Bugis local wisdom, Pacce. In this study, we also ensured the validity, practicality, and effectiveness of the learning model in promoting student character. The current study employed the Plomp & Nieveen research and development (R&D) model. The model was tried out to 32 tenth-grade students at SMA Negeri 1 Pangkajene, Pangkep Regency. The research instruments comprised validation sheets, questionnaires, achievement tests, and character observation sheets. The results showed that the learning model and student worksheets developed in this study were valid in terms of cultural appropriation. The learning model was also practical and effective in improving student cultural awareness. It can be inferred that the learning model developed from the Bugis local wisdom may be used to develop student social awareness.